Role for Oxidative Stress in the Regeneration of Islet Beta Cells?. (1st January 2004) - Haskins, Kathryn; Kench, Jennifer; Powers, Katherine; Bradley, Brenda; Pugazhenthi, Subbiah; Reusch, Jane; McDuffie, Marcia
Abstract : In the nonobese diabetic (NOD) mouse model of type 1 diabetes, we have found that there are increased markers of oxidative stress in islet beta cells in prediabetic animals when compared with control strains. Treatment of these mice with a superoxide dismutase (SOD) mimetic can markedly reduce the level of nitrotyrosine found in islets. In a diabetes-resistant NOD congenic mouse, the NOD.Lc7 mouse, we found increased beta cell proliferation and decreased apoptosis in islets. There are also lower levels of nitrotyrosine in islets of NOD.Lc7 mice than in NOD mice, suggesting that NOD.Lc7 islets are less susceptible to oxidative damage. We hypothesize that there may be a link between the ability of islet cells to regenerate and their resistance to oxidative stress.